Evaluasi Kinerja dan Kelayakan Bundaran Kauman dengan Metode MKJI 1997 - Okta Raqib; M.Hanif Faisal; Firmanilah Kamil (Journal of Research and Inovation in Civil Engineering as Applied Science, 2022)
The study at the Kauman roundabout is essentially motivated by the performance of the intersection, the flow of traffic that occurs causes congestion, especially during rush hours, so it needs further attention. The purpose of this study are determine the effect of unsignalized intersections with roundabouts on capacity, degree of saturation, delays and queuing opportunities that may occured, and the Level of Service (LOS). The research method in data collection is direct observation in the location. The types of data used are both primary and secondary. Primary data, is obtained from direct observation in the location, while secondary data is obtained from related agencies. The basis for solving or analyzing data is using the equations contained in the 1997 Manual Kapasitas Jalan Indonesia (MKJI) to determine the performance value, feasibility and the level of service. The results show that the performance values (DS) on the AB, BC, CD, and DA links are 0.30; 0.39; 0.26; and 0.38. The level of feasibility of the Kauman Roundabout is good in serving traffic flow because the degree of saturation in each link is less than 0.75. Meanwhile, the level of service in all relationships has a B value